The math book : from Pythagoras to the 57th dimension, 250 milestones in the history of mathematics - Pickover, Clifford A. (New York, NY : Sterling Pub., 2009)
This book covers 250 milestones in mathematical history, beginning millions of years ago with ancient "ant odometers" and moving through time to our modern-day quest for new dimensions.
Includes bibliographical references (pages 518-525) and index.
Keywords: Mathematics -- History; Discoveries in science; Mathematics -- Popular works